Genotypes of dengue virus circulate in dengue sentinel surveillance in Indonesia - Reni Herman; Hartanti Dian Ikawati; Arie Ardiansyah Nugraha; Agustiningsih Agustiningsih; Masri Maha Sembiring (Health Science Journal of Indonesia, 2016)
Latar Belakang: Demam berdarah dengue disebabkan oleh infeksi virus dengue (DENV) yang terdiri atas serotipe 1 sampai dengan serotipe 4. Masing-masing serotipe dibedakan lagi menjadi beberapa genotipe. Studi ini dilakukan untuk mendeteksi genotipe DENV yang bersirkulasi di lokasi surveilans sentinel dengue. Metode: Untuk menentukan genotipe dilakukan analisis genetik menggunakan perangkat bioinformatik. Urutan nukleotida yang lengkap dari gen selubung DENV diperoleh melalui amplifikasi genetik menggunakan primer overlapping untuk masing-masing serotipe. Pohon filogenetik dibuat menggunakan perangkat lunak MEGA 6.0, metode Neighbor Joining dengan 1000 replikasi dan parameter Kimura-2. Sekuen nukleotida dari GenBank yang telah diketahui genotype DENV digunakan sebagai referen. Hasil: Jumlah sampel dengan gen selubung DENV yang dapat diamplifikasi adalah 64 dari 204 kasus yang terkonfirmasi. Empat belas sekuen dari DENV-1, 22 sekuen DENV-2, dan 28 sekuens DENV-3. Dari studi ini belum didapatkan sekuen untuk DENV-4. DENV-1 dan DENV-2 masing-masing masuk dalam kelompok genotipe I dan Cosmopolitan, sementara DENV-3 masuk dalam kelompok genotipe I. Kesimpulan: Genotipe  DENV di lokasi surveilans sentinel dengue  sama dengan genotype yang sebelumnya dilaporkan bersirkulasi di Indonesia. (Health Science Journal of Indonesia 2016;7(2):69-74) Kata kunci: surveilans sentinel dengue, virus dengue, genotype   Abstract Background: Dengue hemorrhagic fever was caused by dengue virus (DENV). This virus has four serotypes, DENV-1 to DENV-4, in which each serotype consists of various genotypes. This study present the distribution of DENV genotype circulate in dengue sentinel surveillance sites. Methods: We performed molecular analyses using bioinformatics tools to identify genotype of DENV. Sequencing targeting envelope gene was carried out on DENV-positive samples. Full-length sequence of envelope gene was obtained using overlapping primers for DENV 1, 2, 3 and 4. Phylogenetic tree was generated by Neighbor Joining using MEGA 6.0 with 1000 bootstrap replications and Kimura 2-parameter model.  Known genotype of DENV sequences from Indonesia and other countries obtained from GenBank were included in the analyses as references. Results: A total of 64 complete coding sequences of envelope gene from DENV-1, DENV-2 and DENV-3 were successfully sequenced from 204 confirmed DENV cases. There are fourteen sequences of DENV-1, 22 sequences of DENV-2 and 28 sequences of DENV-3. Unfortunately, there was no complete coding sequence of envelope gene obtained for DENV-4. DENV-1 and DENV-2 were grouped into genotype I and cosmopolitan genotype, respectively. The DENV-3 was grouped into genotype I. These viruses were belongs to various genotypes that have been circulating previously in Indonesia. Conclusion: This finding suggests that the distribution of DENV genotype in sentinel sites remained stable. (Health Science Journal of Indonesia 2016;7(2):69-74) Key words: dengue sentinel surveillance, dengue virus, genotype